Stability analysis of interval time-varying delayed neural networks including neutral time-delay and leakage delay. (September 2018) - Manivannan, R.; Samidurai, R.; Cao, Jinde; Alsaedi, Ahmed; Alsaadi, Fuad E.
Highlights: Some new mathematical technique is adapted together with L-K functionals are estimated its derivative via delay-partitioning approach, which has not been considered yet in stability of model (1) with interval time-varying delays and leakage delays are introduced. Different from others in [12, 15, 16, 18, 21, 22, 27, 33, 44, 47], several numerical examples are presented to illustrate the validity of the main results with a real-world simulation. This implies that the results of the present paper are essentially new. Additionally, Wirtinger double integral inequality (WDII) technique is taken into account to bound the time-derivative of triple integral Lyapunov–Krasovskii functionals (LKFs), which provide more tighter bounding technology to dealing with such LKFs, this technique has been never used in previous literature ****[12, 15, 16, 18, 21, 22, 27, 33, 44, 47], which play an important role in reducing conservatism. ***** Abstract: This paper addresses an improved stability criterion for an interval time-delayed neural networks (NNs) including neutral delay and leakage delay. By proposing a suitable Lyapunov–Krasovskii functionals (LKFs) together with the Auxiliary function-based integral inequality (AFBII) and reciprocally convex approach (RCC) approach. The major purpose of this research is put forward to the consideration of inequality techniques together with a suitable LKFs, and mixed with the Leibniz–Newton formula within the structure of linear matrix inequalities (LMIs). It is amazing that, the leakage delay has a disrupting impact on the stability behaviour of such system and they cannot be neglected. Finally, numerical examples have been demonstrated to showing feasibility and applicability of the developed technique. In addition, the developed stability criteria tested for feasibility of the benchmark problem to explore the real-world application in the sense of discrete time-delay and leakage delay as a process variable in the system model.